2011
DOI: 10.1002/ejic.201001259
|View full text |Cite
|
Sign up to set email alerts
|

Green Wet Chemical Route for the Synthesis of Silver and Palladium Dendrites

Abstract: A novel and very effective wet chemical route for the preparation of metal dendritic nanostructures was developed by starting from VOSO 4 and Ag 2 SO 4 (or K 2 PdCl 4 ) in aqueous solution at room temperature. No template or surfactant was used. VOSO 4 serves as the reducing agent for the silver salt, and the resulting silver nanoparticles and nanocrystallites are then arranged into dendritic structures. The morphologies of the dendrites are found to be heavily influenced both by the molar ratio and the concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…[6][7][8][9] This process, however, also has limited application to non-conductive and flexible substrates. Meanwhile, it has been reported that the dendritic structures of metals, such as those of Cu, 10 Fe, 11 Ag, 12 Ni, 13 PtPb, 14 and NiFe, 15 can be grown in a non-equilibrium state. In their reports, the process requires a long process time of 10-20 h and higher temperatures than 140 uC.…”
mentioning
confidence: 99%
“…[6][7][8][9] This process, however, also has limited application to non-conductive and flexible substrates. Meanwhile, it has been reported that the dendritic structures of metals, such as those of Cu, 10 Fe, 11 Ag, 12 Ni, 13 PtPb, 14 and NiFe, 15 can be grown in a non-equilibrium state. In their reports, the process requires a long process time of 10-20 h and higher temperatures than 140 uC.…”
mentioning
confidence: 99%
“…Silver dendrite also exhibits better sintering and percolation performance in electric conductive composites than silver flakes 4 . The methods available for producing silver dendrite include replacement reactions 6 , electrochemical 7 9 , solvothermal 10 , oxidation reduction 4 , wet chemical 11 , and template reduction 12 methods, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of dendritic structure, it is generally accepted that the nonequilibrium condition in which a kinetic factor dominates the thermodynamic one would cause the anisotropic crystal growth. Several models, including the deposition, diffusion, and aggregation (DDA), the diffusion-limited aggregation (DLA), oriented attachment (OA), and the cluster–cluster aggregation (CCA), have been proposed for the formation of silver dendrites, where DLA and the oriented attachment or a combination of those two have been more popular than other mechanisms to interpret the growth process of silver dendrites in solution. , On the one side, DLA refers to the formation of fractal structures through random aggregation and the asymmetric growth of nanoparticles when the growth rate is limited by the diffusion rate of solute atoms (also identified as random walkers) to the reaction interface. On the other side, oriented attachment is the process of the spontaneous self-assembly/alignment of adjacent particles so that they share a common crystallographic orientation, which leads to the joining of these particles at a planar interface .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Among various metallic nanostructures, silver hierarchical structures (mainly dendrites), possessing a high surface area along with nanoscale narrow gaps and sharp edges, have become prominent due to their significant potential use in surface-enhanced Raman scattering (SERS), catalytic, biosensing, , and super-hydrophobic surfaces , applications. As of today, numerous silver hierarchical nanostructures with diverse structural features and applications have been fabricated through different synthesis methods including electrochemical deposition, electroless redox reaction, , wet chemical route using reducing agents in aqueous solution, , photocatalytic reduction, , sono-electrochemical deposition, , photoreduction by ultraviolet irradiation, etc. However, each of the mentioned methods are inflicted to a degree by some deficiencies, such as requiring special equipment, time-consuming (up to 30 d), impurity, using highly hazardous materials (e.g., HF), needs of seed particles and templates, multiple capping agents, multiple synthetic steps, difficulties to remove the templates or surfactants from the surface of the silver nanostructure products, high-cost or low-yield restrictions, and poor reproducibility, to name a few.…”
Section: Introductionmentioning
confidence: 99%